Political-Social Achievements of Religious Intellectualism in Iran and Egypt - Ebrahim Qasempoor; Aliakbar Amini; Morteza Manshadi (سپهر سیاست, 2021)
The present study, relying on the ideas of some religious intellectuals such as Seyyed Jamāl as a theorist of religious intellectualism in the Islamic world including Iran and Egypt, 'Allāma Nā'ini as an Iranian reformist intellectual, and Sheykh Mohammad 'Abdah as an Egyptian reformist, aims to answer what were the political-social achievements of religious intellectual movement in Iran and Egypt. The method of study was descriptive analysis and the results showed that religious intellectualism in the 19th century Iran has had some achievements in Iran like propagating rationalism, and creating modern structures such as parliament, law, and court. It also has brought about some outcomes in Egypt, like propagating rationalism, starting reformism, modernism movement and its manifestations such as newspapers and new schools, changing the attitude to women's rights, nationalism, and secularism.